La transe vaudouesque : un syndrome de déviance psycho-culturelle - Douyon, Emerson (Acta Criminologica, 1969)
AbstractSPIRIT POSSESSION:A PSYCHO-CULTURAL SYNDROME OF DEVIANT BEHAVIOURThe Voodoo trance represents the principal aspect of deviant behaviour among coloured people. This tricky phenomenon, always considered a challenge to any scientific explanation, was subjected to an experimental analysis.We wanted to find out what the trance performers have in common and to check whether a typical psychological structure could be associated with their deviant behaviour.The sample included forty-four subjects divided into three categories: a) a ritual group, b) a non-ritual group, c) a control group. No male subject was used because very few men are ever possessed by spirits. Every subject was submitted to a preliminary medical check-up (physical, neurological and laboratory tests), and to a series of psychological examinations (Raven, Goldstein-Scheerer, Sacks, Rorschach, autobiographical and personality questionnaires).The findings of the neurologist, the pathologist and the laboratory were completely negative as far as somatic predisposition to trance was concerned. But evidence of significant differences between the experimental and the control groups was demonstrated on the basis of personality tests and autobiographical questionnaires.Spirit possession, to be induced, requires not only specific conditioning experiences, but also a disturbed, anxious and depressed personality. The non-ritual form does not imply a higher degree of pathology.An intimate relationship between possession, states of depression and suicide has been indicated. The trance seems to be the only alternative for the neutralization of hostile feelings, either directed to the self or to others. The inhibitory effect of possession could finally prove to be a factor in reducing criminality in Haiti.